Diagnosing AL and ATTR amyloid cardiomyopathy: a multidisciplinary approach - Siepen, Fabian aus dem; Hansen, Timon (Journal of Clinical Medicine, 2024)
Amyloidosis with cardiac involvement is a fatal disease leading to progressive heart failure. The most common forms of amyloidosis with cardiac involvement are light chain (AL) and transthyretin (ATTR) amyloidosis. To allow effective specific treatment for both forms, precise and early diagnosis is important. This review focuses on diagnostic approaches for AL and ATTR amyloidosis with cardiac involvement, including different strategies, the role of imaging and biomarkers and possible pitfalls.
Gesehen am 27.03.2025